PKM Pelatihan Integrating Ms. Word, Ms. Excel, dan Ms. PowerPoint for Office Management Bagi Guru SMP Di Kabupaten Takalar: PKM Pelatihan Integrating Ms. Word, Ms. Excel, dan Ms. PowerPoint for Office Management Bagi Guru SMP Di Kabupaten Takalar - Ruslan; Nurwati Djam'an; Sahid (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
This Integrating Ms. Word, Ms. Excel, and Ms. PowerPoint for Office Management training aims to train junior high school teachers in Takalar to optimize Office Management. Solutions to problems that have been achieved in this training are: (1) Introducing Office Management features; (2) Improving teachers' ability to apply Office Management features; (3) Increasing confidence in teachers in implementing Office Management in their work activities; (4) Improve teachers' knowledge and skills using application programs such as Automatic Table of Contents, Fun with Pictures, Page numbering, Design Template, Embedding video, hyperlinks, running text with music, and Calculations in Excel. Furthermore, this training can increase the participant’s knowledge in terms of creating automatic attendance in Microsoft Excel